2016
DOI: 10.3899/jrheum.151101
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Psoriatic Arthritis Fulfilling the Minimal Disease Activity Criteria Do Not Have Swollen and Tender Joints, but Have Active Skin

Abstract: A minority of patients with PsA fulfilling the MDA criteria presented active joints, but half had active skin. Visual analog scale scores and the PASI prevented patients from achieving MDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Pain was also the most commonly unmet MDA criterion in a study from the Biologic Treatment Registry Across Canada registry [ 22 ]. The influence of pain on therapeutic response in PsA is consistent with findings from our study of patients with RA, in which pain showed a high correlation with therapeutic response as assessed by DAS28 [ 23 ], and with a recent study of 83 patients with PsA who presented to a hospital clinic in Argentina, which also found that the pain score criterion was the least likely to be achieved (29% of patients overall and 56% of patients with MDA) [ 24 ]. In contrast, BSA ⩽3% and enthesitis showed only low correlations with MDA and did not correlate well with other MDA criteria.…”
Section: Discussionsupporting
confidence: 89%
“…Pain was also the most commonly unmet MDA criterion in a study from the Biologic Treatment Registry Across Canada registry [ 22 ]. The influence of pain on therapeutic response in PsA is consistent with findings from our study of patients with RA, in which pain showed a high correlation with therapeutic response as assessed by DAS28 [ 23 ], and with a recent study of 83 patients with PsA who presented to a hospital clinic in Argentina, which also found that the pain score criterion was the least likely to be achieved (29% of patients overall and 56% of patients with MDA) [ 24 ]. In contrast, BSA ⩽3% and enthesitis showed only low correlations with MDA and did not correlate well with other MDA criteria.…”
Section: Discussionsupporting
confidence: 89%
“…A previous study reported a highly active skin component still present in patients otherwise meeting MDA criteria; however, details of PsA therapy were not presented. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 14 However, the attainment of individual MDA components in MDA achievers has not been extensively evaluated. 15 Identification of MDA components that are difficult to achieve may ascertain clinical or pathological factors that merit future attention in disease management strategies. Additionally, there is limited understanding of patient and disease characteristics that predict MDA achievement over longer term and of other potential benefits associated with achievement of MDA.…”
Section: Introductionmentioning
confidence: 99%
“…In registries and observational studies, demographic characteristics such as younger age and male sex, lower functional impairment at baseline (assessed by the Bath Ankylosing Spondylitis Functional Index and HAQ), low disease activity at baseline, and other factors such as shorter symptom duration and greater general well-being (assessed by global VAS) have been reported as predictors of achieving MDA upon treatment with TNF inhibitors 24,26,31,32 .…”
Section: Predictors Of Achieving Mdamentioning
confidence: 99%